Pengaruh Self Terapi Akupresur Pericardium 6 (PC 6) Oleh Ibu Hamil terhadap Nausea and Vomiting of Pregnancy (NVP) di TPMB Yulis Indriana Kota Malang - Nur Rizka Mardhatillah Halik; Tavip Dwi Wahyuni; Asworoningrum Yulindahwati (STIKES Columbia Asia Medan, 2025)
Symptoms of nausea and vomiting (emesis gravidarum) are common complaints in the early trimester. However, if it continues without treatment, this condition can develop into hyperemesis gravidarum which risks causing nutritional deficiencies in the mother and inhibiting fetal growth. (Intraupterine Growth Retardation /IUGR). Treatment can be done non-pharmacologically with acupressure. Neiguan point (pericardium 6) is considered useful to reduce nausea and vomiting. This study aims to determine the effect of self-acupressure therapy pericardium 6 by pregnant women on Nausea and Vomiting of Pregnancy (NVP). The research design used a pre-experiment with a one group pretest-posttest design without control group. The sampling technique used simple random sampling with a sample of 38 pregnant women Trimester I K1 who experienced nausea and vomiting, no history of gastritis. Data collection using the Pregnancy-Unique Quantification of Emesis and Nausea (PUQE-24) observation sheet The results of statistical tests using the Wilcoxon Signed Rank Test showed the p value was (0.000). The research hypothesis proposed is an alternative hypothesis, where Ha = p < 0.05, meaning that there is an effect of self-acupressure therapy pericardium 6 (PC 6) by pregnant women on Nausea and Vomiting of Preganancy (NVP) at TPMB Yulis Indriana Malang City. Pericardium 6 acupressure is considered effective and safe for pregnant women.